Adult neurogenesis in Alzheimer's disease. Issue 4 (7th February 2023) - Choi, Se Hoon; Tanzi, Rudolph E.
Abstract: Alzheimer's disease (AD) is the most common form of age‐related dementia, characterized by progressive memory loss and cognitive disturbances. The hippocampus, where adult hippocampal neurogenesis (AHN), a relatively novel form of brain plasticity that refers to the birth of new neurons, occurs, is one of the first brain regions to be affected in AD patients. Recent studies showed that AHN persists throughout life in humans, but it drops sharply in AD patients. Next questions to consider would be whether AHN impairment is a contributing factor to learning and memory impairment in AD and whether restoring AHN could ameliorate or delay cognitive dysfunction. Here, we outline and discuss the current knowledge about the state of AHN in AD patients, AHN impairment as a potentially relevant mechanism underlying memory deficits in AD, therapeutic potential of activating AHN in AD, and the mechanisms of AHN impairment in AD.